Factors related to anemia in children from 6 to 36 months in a rural area of Huánuco, Perú - Ibazeta-Estela, Ericka A. (2019)
Introduction: Anemia is a common laboratory finding in childhood, affecting 20% ​​of children in developed countries. There are 293 million children under the age of five with anemia in the world. The objective of the present study was to analyze the factors that condition the low levels of hemoglobin in children from 6 to 36 months in the District of Churubamba 2017. Material and Methods: An observational, analytical, retrospective study was conducted in children from 6 to 36 months of age with low levels of hemoglobin, belonging to a social support program. Results: Significant difference was found between low levels of knowledge of the mother on nutrition [p = 0.037, RP 1.27 (95% CI 1.04-1.55)], low socioeconomic level [p = 0.000, RP 1 , 54 (95% CI 1.31-1.81)], affiliation to the JUNTOS program [p = 0.000, RP = 1.53 (95% CI 1.27-1.84)], the child's age [p. = 0.012, RP = 1.35 (95% CI 1.03-1.76)], the gender of the children [p = 0.000, RP = 1.47 (95% CI 1.16-1.86)] , hand washing [p = 0.006, RP = 1.38 (95% CI 1.15-1.67)] and basic sanitation [p = 0.000, RP 2.80 (95% CI 1.91-4 , 09)]. Conclusions: There is an association between the low nutritional knowledge of the mother, the low socioeconomic level and the intervention of the JUNTOS program, to present low levels of hemoglobin in children from 6 to 36 months.